Fostering a Healthy Psychosocial Environment for Adolescents: The Role of Health Promoting School in Sukoharjo District - Noviyanti, Tausyiah Rohmah; Sulistyowati, Muji; Tiber Raniar Inner Beauty Bilqis; Anggit Wirama Siwidati; Adin Nasichah (Universitas Airlangga, 2025)
Background: Adolescent mental health is increasingly a global concern, particularly within the school environment. This study aims to analyze the role of schools in supporting mental health and creating a healthy psychosocial environment as part of health promotion efforts in Sukoharjo District. Methods: This study uses an evaluation study approach with qualitative method was used, with in-depth interviews conducted with 25 informants from 10 junior high schools, selected through purposive sampling. Data were analyzed thematically, based on the WHO's Health Promoting School elements and CDC’s 6 mental health strategies in schools. Results: The school has implemented several efforts, such as counseling by providing guidance services with counseling guidance teachers (BK), spiritual activities with the aim of encouraging to focus on student awareness and counseling activities, character education, increasing welfare by providing activities such as student councils and family involvement to increase the impact of interventions on the level of social anxiety in adolescent environments although not all mental health strategies are explicitly implemented. Conclusion: This study highlights the importance of social support and a healthy environment in promoting mental health. Schools are advised to strengthen collaboration with mental health professionals and improve access to mental health services for students.